Determinan Kesejahteraan Keluarga Nelayan di Desa Tanjung Benoa Kabupaten Badung, Bali - Sanjaya, Putu Krisna Adwitya; Jayanthi, Ni Kadek Eka; Pradnyani, Ni Luh Mas Aprilia; Cahyani, Ni Kadek Anggita Dwi (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2024)
This research aims to analyze the determinants of the welfare of fishing families in Tanjung Benoa Village, Bali. This research uses a quantitative approach. The data analysis method used is descriptive analysis and quantitative analysis of structural equations using Smart-PLS. This research used all 140 people who make their living as fishermen. This research found that income, family consumption, use of fishing technology and level of education have a positive and significant effect on the welfare of fishing families in Tanjung Benoa, Badung Regency. Fishing technology does not moderate the influence of income on the welfare of fishing families in Tanjung Benoa. This research provides related implications regarding increasing income which has the potential to significantly improve family welfare, it is important for fishing families to manage spending patterns for consumption effectively, increasing access and quality of education for fishermen will be a strategy in an effort to simultaneously improve welfare. The variables income, consumption and education can be used as parameters for policy makers to make concrete policies as an effort to improve the welfare of fishing families in Tanjung Benoa Village, Badung.